EFFECTS OF SELECTED COMPANY-SPECIFIC VARIABLES IN THE DETERMINATION OF COMPANY LEVERAGE: EVIDENCE FROM TEXTILE INDUSTRY OF BANGLADESH - Arif, Md Asaduzzaman (Asian Finance & Banking Review, 2021)
The purpose of this study is to investigate the effects of profitability, liquidity, size, tangibility, and asset turnover on the leverage of the textile industry of Bangladesh. This paper analyzed 20 companies out of 56 companies listed in the Dhaka Stock Exchange. The data set is for the periods from 2016 to 2019. To find the effects on the dependent variable, the Fixed Effects Model has been used which has been selected using the Hausman test. To test heteroskedasticity, the Breusch-Pagan heteroskedasticity test has been used. The study found size, profitability, and tangibility having a significant effect. While size and tangibility have a positive impact on leverage, profitability has a negative impact. The findings are diversified in nature. The results are not all consistent with the previous studies conducted in different developing countries. So, the policymakers should have in-depth insights while making decisions.